Modified waste EVA (Ethylene Vinyl Acetate), modification method thereof, EVA product prepared from modified waste EVA and preparation method of EVA product
Through supercritical CO2 treatment and microcrystalline cellulose modification technology, the poor reprocessing performance and compatibility of waste EVA are solved, and its refoaming performance and compatibility are significantly improved, achieving more efficient waste EVA reprocessing use.
Patent Information
- Application Number
- CN202411477903.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
AI Technical Summary
Changes in the molecular chain structure of waste EVA lead to poor reprocessing performance, compatibility problems and insufficient refoaming performance, which limits its application in high-end fields.
Using supercritical CO2 treatment and microcrystalline cellulose modification methods, the supercritical CO2 expansion and cross-linking of waste EVA are used, and nanocellulose is generated in situ as a reinforcement and compatible agent, combined with plasma grafting technology, Improve the mechanical properties and compatibility of waste EVA.
The refoaming performance and compatibility with the new EVA are significantly improved, forming a uniform nanocellulose distribution, enhancing the mechanical properties of the composite material, and achieving more efficient recycling of waste EVA.
Smart Images

Figure BDA0005096597080000071 
Figure BDA0005096597080000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer material recycling, and in particular to a modified waste EVA and a modification method thereof, an EVA product prepared by using the modified waste EVA and a preparation method thereof. Background Art
[0002] EVA (ethylene-vinyl acetate copolymer) is a widely used polymer material. It is widely used in shoe soles, packaging materials, solar panel backplanes, etc. due to its soft texture, strong resilience, and chemical corrosion resistance. However, with the widespread use of EVA products, the recycling of waste EVA has become increasingly prominent, becoming one of the key challenges for environmental protection and sustainable development.
[0003] At present, the recycling of EVA waste faces many technical difficulties. First of all, since the waste EVA has been treated with foaming and cross-linking, coupled with long-term use, its molecular chain structure will change significantly, such as molecular chain breakage and increased cross-linking degree. These changes directly affect the physical and mechanical properties and reprocessing performance of waste EVA, making it difficult to directly recycle waste EVA to achieve the same mechanical strength and foaming effect as new EVA materials, limiting its application in high-end fields. Secondly, the compatibility problem between waste EVA and new EVA is also an important factor restricting recycling and reuse. Since the molecular chain structure of waste EVA has changed, it is easy to phase separate from new EVA during the blending process, resulting in uneven mixing, which in turn affects the uniformity and overall performance of the final product. This poor compatibility problem not only reduces the appearance quality of the product, but may also affect the service life and safety of the product. Furthermore, although traditional waste EVA recycling methods, such as mechanical crushing and hot melting, can achieve the reuse of waste EVA to a certain extent, these methods are often difficult to effectively open the cross-linked network structure of EVA during the processing process. The existence of the cross-linked network structure limits the re-foaming performance of waste EVA, making it difficult for the recycled material to form an ideal pore structure during the foaming process, thereby affecting the lightweight and thermal insulation performance of the product. Summary of the invention
[0004] In order to improve the poor re-foaming performance of waste EVA and the poor compatibility with new EVA, the present application provides a modified waste EVA and a modification method thereof, an EVA product prepared using the modified waste EVA and a preparation method thereof.
[0005] In the first aspect, the present application provides a method for modifying waste EVA, using the following technical solution: A method for modifying waste EVA comprises the following steps: First, waste EVA is placed in supercritical CO 2The waste EVA is subjected to supercritical treatment in an environment, and then the waste EVA is modified by using microcrystalline cellulose to obtain modified waste EVA.
[0006] This application introduces supercritical CO 2 Supercritical treatment of waste EVA can effectively expand and partially de-crosslink the waste EVA, thereby improving its re-foaming performance; the waste EVA can be further modified using microcrystalline cellulose, and the nanocellulose generated in situ on the waste EVA can be used as a reinforcing agent and compatibilizer to improve the compatibility of waste EVA with new EVA and the mechanical properties of the composite material.
[0007] Compared with the method of directly adding nanocellulose, the nanocellulose generated in situ on the waste EVA in the present application is more evenly and dispersedly distributed in the waste EVA.
[0008] Optionally, the conditions of the supercritical treatment are as follows: The temperature is 40-60°C, the pressure is 15-25MPa, and the time is 2-4h.
[0009] Since carbon dioxide changes its properties in a supercritical state, its density is close to that of a liquid, its viscosity is close to that of a gas, and its diffusion coefficient is 100 times that of a liquid, it has an amazing solubility and can dissolve a variety of substances. 2 To treat waste EVA, CO 2 It can penetrate into the interior of the EVA material, dissolve and extract small molecular pollutants, additive residues and some degradation products. These dissolved substances can then be extracted from the supercritical CO by reducing the pressure or temperature. 2 In addition, under supercritical conditions, CO 2 The molecules can penetrate into the molecular chains of EVA, changing their arrangement and interaction forces, thereby improving the processing performance and physical properties of waste EVA to a certain extent and de-crosslinking part of the waste EVA.
[0010] In addition, CO 2 As a naturally occurring gas, it is non-toxic and harmless, and can be recycled during the treatment process without causing any pollution to the environment. It will not introduce new impurities into the waste EVA, making it easier to re-foam it in the future. Compared with the traditional chemical de-crosslinking method, this application does not require the use of organic solvents, and the treated CO 2 It can be recycled and complies with the principles of green chemistry.
[0011] Optionally, the method further comprises a plasma treatment performed simultaneously with the supercritical treatment, wherein the plasma treatment is used to induce grafting of functionalized monomers onto the waste EVA.
[0012] Optionally, the functionalized monomer is acrylic acid or acrylamide.
[0013] Optionally, the functionalized monomer is used in an amount of 0.5 wt.% to 2.0 wt.%.
[0014] The present invention utilizes plasma-induced grafting to introduce specific functional groups while removing crosslinks, thereby enhancing the compatibility and interfacial bonding strength between waste EVA and new EVA or other components. 2 The high permeability enables plasma to act more deeply into the EVA material, achieving more uniform and in-depth modification.
[0015] Optionally, the conditions of the plasma treatment are specifically as follows: The output power of the plasma generator is 50-200W, the gas used is a mixed gas composed of Ar and O2 in a volume ratio of 7:3-9:1, and the processing time is 15-45min.
[0016] Ar (argon) is an inert gas. The plasma generated after ionization will not react chemically with the waste EVA. Its main function is to clean the impurities of the waste EVA and roughen the surface. 2 The plasma generated by ionization of (oxygen) can activate the material and improve the surface properties of the material; when performing plasma treatment, please use Ar and O 2 The mixed gas can use oxygen to provide additional oxidizing capacity, which helps to modify materials more efficiently and promote the foaming ability of recycled EVA. At the same time, the stability of argon is used to control the properties of the plasma to prevent over-reaction and damage.
[0017] By precisely adjusting the parameters of plasma treatment, the degree of de-crosslinking of EVA can be precisely controlled, thereby optimizing its re-foaming performance.
[0018] Optionally, the specific steps of modifying the waste EVA using microcrystalline cellulose are: The waste EVA is mixed with the microcrystalline cellulose, water and cellulase are added thereto, the pH value is adjusted to 4.8-5.2, and an enzymatic hydrolysis reaction is carried out under stirring conditions; After the enzymatic hydrolysis reaction is completed, the reaction temperature is rapidly raised to 90° C. and maintained for 10 minutes to ensure that the cellulase is completely inactivated, and then the product obtained by the reaction is dried to obtain the modified waste EVA.
[0019] Optionally, the mass ratio of the waste EVA to the microcrystalline cellulose is 1-3:20.
[0020] Optionally, the mass ratio of the microcrystalline cellulose to the water is 50:1-5.
[0021] Microcrystalline cellulose is a linear polysaccharide. It is a free-flowing, extremely fine short rod-shaped or powdery porous particle of natural cellulose hydrolyzed to the limiting degree of polymerization (LODP) by dilute acid. Microcrystalline cellulose is decomposed into nano-scale cellulose by enzymatic reaction using cellulase and microcrystalline cellulose. Nanocellulose is generated in situ in the EVA matrix and evenly dispersed, acting as a reinforcing agent and compatibilizer. Nanocellulose has a high specific surface area and excellent mechanical properties. It can improve the mechanical properties and compatibility of composite materials by forming a physical cross-linked network or hydrogen bonding with EVA molecular chains.
[0022] Optionally, the enzymatic activity of the cellulase is 50-100 FPU / g, and the added amount of the cellulase is 0.5%-2% of the mass of the microcrystalline cellulose.
[0023] Optionally, the cellulase is selected from one or more of endoglucanase (Endo-β-1,4-glucanase), exoglucosidase (Exo-β-1,4-glucosidase), and cellobiohydrolase (Cellobiase).
[0024] Optionally, the cellulase is obtained by mixing endoglucanase, exoglucosidase and cellobiohydrolase in a mass ratio of 1:1:1.
[0025] Optionally, the temperature of the enzymatic hydrolysis reaction is 54-58°C, the time is 4-6h, and the stirring speed is 100-200rpm.
[0026] According to the above definition, the compounded cellulase can effectively degrade the cellulose molecules and reduce their degree of polymerization, thereby generating smaller cellulose fragments, thereby obtaining nanocellulose to be used as a reinforcing agent and compatibilizer.
[0027] In the second aspect, the present application provides a modified waste EVA, using the following technical solution: A modified waste EVA is prepared by adopting the modification method.
[0028] The modified waste EVA prepared by the above modification method has most of its internal cross-linked network structure de-crosslinked, so the modified waste EVA has good re-foaming performance, and has good compatibility and interface bonding strength with new EVA. In addition, no impurity elements are introduced into the modified waste EVA obtained by the above modification method, and it can be widely used in EVA products again.
[0029] In a third aspect, the present application provides an EVA product prepared using the modified waste EVA, using the following technical solution: An EVA product prepared by using modified waste EVA comprises the following raw materials in parts by weight: Modified waste EVA 40-60 parts, EVA 30-50 parts, foaming agent 2-4 parts, cross-linking agent 1-3 parts, seaweed powder 5-10 parts, processing aid 1-5 parts.
[0030] It should be emphasized that the "EVA" in the above scheme refers to brand new EVA that has not been foamed and treated by the modification method described in this application, and the application document does not emphasize whether it is modified waste EVA or waste EVA, and the "EVA" mentioned refers to this brand new EVA, and the polyethylene content therein is 20%-40%.
[0031] Optionally, the particle size of the seaweed powder is 50 microns.
[0032] As a natural, renewable bio-based filler, the addition of seaweed powder can improve the environmental friendliness and sustainability of composite materials. The particle size of seaweed powder is limited to about 50 microns, which can ensure good dispersion and compatibility with EVA materials, while not being too small to affect its effect as a filler.
[0033] Optionally, the specific surface area of the seaweed powder is 10-50m 2 / g.
[0034] Controlling the specific surface area of seaweed powder within the above range can help improve its water absorption and interaction with EVA materials.
[0035] Optionally, the water content of the seaweed powder is below 5% to avoid adverse effects on the EVA foaming process.
[0036] Optionally, the purity of the seaweed powder is ≥95% to ensure the consistency and controllability of the performance of the EVA product.
[0037] Optionally, the processing aid is stearic acid and / or zinc oxide.
[0038] Optionally, the foaming agent is selected from one or more of azo compounds, hydroxy fatty acid salts and carbonates.
[0039] Optionally, the crosslinking agent is selected from one or more of sulfur, peroxide, isocyanate, silane crosslinking agent and silane resin.
[0040] In a fourth aspect, the present application provides a method for preparing an EVA product, using the following technical solution: A method for preparing the EVA product comprises the following steps: The modified waste EVA is mixed with other raw materials in proportion, and subjected to banburying treatment and foaming treatment to prepare EVA products.
[0041] Optionally, the conditions of the banburying treatment are as follows: The upper push bolt pressure is 0.5-0.6MPa, the rotation speed is 20-40rpm, and the mixing treatment time is 15-20min.
[0042] Optionally, the specific steps of the foaming treatment are as follows: Place the mixed material obtained by kneading in a foaming mold; raise the mold temperature to 160-180°C, apply an initial pressure of 5-8MPa, maintain the temperature and gradually reduce the pressure to 1-2MPa, and maintain for 10-15 minutes; quickly cool to 80-100°C, and gradually increase the pressure to 10-15MPa, and maintain for 5-8 minutes; continue to cool to room temperature to complete the foaming process.
[0043] Optionally, the preparation method of the EVA product further comprises a heat setting treatment after the foaming treatment, and the specific conditions of the heat setting treatment are: a temperature of 85-95° C. and a time of 3-5 hours.
[0044] In summary, the present application includes at least one of the following beneficial effects: 1. This application introduces supercritical CO 2 Supercritical treatment of waste EVA can effectively expand and partially de-crosslink the waste EVA, thereby improving its re-foaming performance; waste EVA can be further modified using microcrystalline cellulose, and the nanocellulose generated in situ on the waste EVA can be used as a reinforcing agent and compatibilizer to improve the compatibility of waste EVA with new EVA and the mechanical properties of the composite material.
[0045] 2. This application uses plasma-induced grafting to introduce specific functional groups while de-crosslinking, thereby enhancing the compatibility and interfacial bonding strength between waste EVA and new EVA or other components. By simultaneously performing plasma treatment and supercritical treatment, supercritical CO 2 The high permeability enables plasma to act more deeply into the EVA material, achieving more uniform and in-depth modification. DETAILED DESCRIPTION
[0046] Preparation Example 1 Preparation Example 1 provides a method for preparing modified waste EVA using waste EVA, which specifically includes the following steps: First, the waste EVA was cleaned, dried and crushed to 100 mesh, and then the treated waste EVA was placed in a high-pressure reactor, and CO was introduced into the high-pressure reactor. 2, raise the temperature to 55°C and the pressure to 23MPa, and maintain for 2.5h; wait for supercritical CO 2 After the treatment is completed, slowly release the pressure and dry the treated waste EVA for later use; The treated waste EVA and microcrystalline cellulose are mixed in a mass ratio of 3:20, and then water and cellulase accounting for 1% of the mass of the microcrystalline cellulose are added thereto, wherein the mass ratio of water to microcrystalline cellulose is 30:1, the pH value is adjusted to 5, and an electric stirrer is used to stir for 5 hours at a temperature of 55°C and a stirring speed of 100 rpm to carry out an enzymatic hydrolysis reaction, wherein the cellulase is obtained by mixing endoglucanase, exoglucosidase, and cellobiohydrolase in a mass ratio of 1:1:1; after the enzymatic hydrolysis reaction is completed, the reaction temperature is quickly raised to 90°C and maintained for 10 minutes to ensure that the cellulase is completely inactivated, and then the reaction product is dried using a vacuum dryer to obtain modified waste EVA.
[0047] Preparation Example 2 Preparation Example 2 provides a method for preparing modified waste EVA using waste EVA, which specifically includes the following steps: First, the waste EVA is washed, dried and crushed to 100 mesh, and then the treated waste EVA and functionalized monomer are added to a high-pressure reactor equipped with a plasma generator; CO is introduced into the high-pressure reactor. 2 , the temperature was raised to 55°C, the pressure was raised to 23 MPa, and maintained for 2.5 h; then the plasma generator was started, and the supercritical CO 2 Low-temperature plasma is generated in the environment; the power of the plasma generator is 150W, the processing time is 30 minutes, the working gas is Ar:O2=8:2, the added functionalized monomer is acrylic acid, and the added amount is 1% of the mass of the waste EVA; wait for supercritical CO 2 After the treatment is completed, slowly release the pressure and dry the treated waste EVA for later use; The treated waste EVA was mixed with microcrystalline cellulose in a mass ratio of 3:20, and then water and cellulase accounting for 1% of the mass of the microcrystalline cellulose were added thereto, wherein the mass ratio of water to microcrystalline cellulose was 35:1, the pH value was adjusted to 5, and an electric stirrer was used to stir for 5 hours at a temperature of 55°C and a stirring speed of 100 rpm to carry out an enzymatic hydrolysis reaction, wherein the cellulase was obtained by mixing endoglucanase, exoglucosidase and cellobiohydrolase in a mass ratio of 1:1:1; after the enzymatic hydrolysis reaction was completed, the reaction temperature was quickly raised to 90°C and maintained for 10 minutes to ensure that the cellulase was completely inactivated, and then the reaction product was dried using a vacuum dryer to obtain modified waste EVA.
[0048] Preparation Example 3 Preparation Example 3 is substantially the same as Preparation Example 2, except that the functionalized monomer added for plasma treatment in Preparation Example 3 is acrylamide, and the added amount thereof is 1.5% of the mass of the waste EVA.
[0049] Preparation Comparative Example 1 Preparation Comparative Example 1 provides a method for preparing modified waste EVA using waste EVA, which specifically includes the following steps: First, the waste EVA is cleaned, dried and crushed to 100 mesh, and then the treated waste EVA is placed in a high-pressure reactor equipped with a plasma generator; CO is introduced into the high-pressure reactor. 2 , raise the temperature to 55°C and the pressure to 23MPa, and maintain for 2-4h; wait for supercritical CO 2 After the treatment is completed, the pressure is slowly released, and the treated waste EVA is dried for standby use to obtain modified waste EVA.
[0050] Example 1 Example 1 provides an EVA insole prepared using modified waste EVA, the component formula of which is: 55 parts of the modified waste EVA prepared in Preparation Example 1, 30 parts of EVA, 7 parts of seaweed powder (particle size 50 μm), 3 parts of a foaming agent (azodicarbonamide), 2 parts of a cross-linking agent (diisopropylbenzene peroxide), and 3 parts of a processing aid (stearic acid). The preparation method is as follows: Put all the raw materials into an internal mixer, mix for 15-20 minutes at a bolt top pressure of 0.5-0.6 MPa and a rotation speed of 20-40 rpm to obtain a mixture; The mixture is then placed in a dynamic pressure foaming mold for controlled pressure foaming. First, the mold temperature is raised to 175°C, and an initial pressure of 6.5 MPa is applied at the same time; the temperature is maintained, and the pressure is gradually reduced to 1.2 MPa, and maintained for 15 minutes to achieve controlled foaming; the temperature is quickly reduced to 85°C, and the pressure is gradually increased to 13 MPa, and maintained for 7 minutes; and the mold is continued to cool to room temperature to complete the molding.
[0051] Finally, the foamed material is subjected to heat setting treatment at 85-95°C for 3-5 hours.
[0052] Example 2-3 Example 2-3 is basically the same as Example 1, the only difference is that the modified waste EVA used in Examples 2-3 comes from Preparation Examples 2-3 respectively.
[0053] Comparative Example 1 Comparative Example 1 is substantially the same as Example 1, except that the modified waste EVA used in Comparative Example 1 is obtained from the preparation of Comparative Example 1.
[0054] Comparative Example 2 Comparative Example 2 provides an EVA insole prepared from waste EVA, wherein the waste EVA is cleaned, dried, crushed to 100 mesh, and then mixed with EVA at a mass ratio of 1:1. The mixing and foaming treatments are the same as those in Example 1.
[0055] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the EVA insole is prepared by a conventional pressing and foaming process. The specific steps are as follows: First, prepare the raw materials, the types and proportions of the raw materials are the same as those in Example 1.
[0056] Put all the raw materials into an internal mixer to ensure that all the ingredients are evenly mixed; heat the evenly mixed raw materials to 120°C to decompose the chemical foaming agent to produce gas; set the heating time to 3 minutes and the temperature to 120°C to form uniform small bubbles in the material to form a pre-foamed material; fill the pre-foamed material into a molding mold, heat the mold (temperature is 170°C) and apply a pressure of 2MPa to make the material completely fill the mold and form the desired shape; cool and solidify in the mold to make the polymer completely harden and complete the molding.
[0057] Performance Testing The EVA products prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing. The specific testing methods and test results are shown in Table 1.
[0058] Table 1 Performance test methods and results From the results in Table 1, it can be seen that the density of Examples 1-3 is significantly lower than that of Comparative Examples 1-2, indicating that the use of supercritical CO 2 The treatment and modification of waste EVA using microcrystalline cellulose greatly improves the re-foaming ability of the waste EVA. In comparison, the density of Example 2 is lower, indicating that adding plasma treatment on the basis of Example 1 can promote the waste EVA to achieve a higher degree of de-crosslinking, thereby obtaining a better re-foaming ability.
[0059] In addition, it can be seen that Examples 1-3 exhibit excellent mechanical properties, especially tensile strength and elongation at break, which indicates that the use of supercritical CO for waste EVA 2 Treating and modifying waste EVA with microcrystalline cellulose can improve the compatibility between waste EVA and new EVA. Compared with Example 1, the active groups introduced by plasma treatment in Examples 2 and 3 further enhance the reactivity of the waste EVA, thereby promoting the formation of more cross-linked network structures during the re-foaming process.
[0060] It can also be seen from Table 1 that, compared with Comparative Examples 1-3, Examples 1-3 also exhibit lower compression permanent deformation and lower coefficient of variation of bubble size. The lower compression permanent deformation indicates that the EVA insoles prepared in Examples 1-3 have better elastic recovery properties and therefore have a longer service life, while the lower coefficient of variation of bubble size indicates that the EVA insoles prepared in Examples 1-3 have a more uniform foaming structure.
[0061] Comparing Example 1 with Comparative Example 3, the difference between the two lies in the different foaming processes. Since the foaming process of Example 1 is more precise and controllable, the density of the EVA insole obtained in Example 1 is lower, and the foaming is more uniform.
[0062] In summary, this application utilizes supercritical CO 2 The de-crosslinking pretreatment technology of waste EVA with auxiliary microcrystalline cellulose significantly improved the recycling performance of waste EVA, which was significantly different from the traditional method and the simple supercritical CO 2 Compared with traditional pretreatment methods, this method not only achieves a higher waste utilization rate, but also brings significant improvements in density, mechanical properties, comfort and durability. This innovative pretreatment method provides a new technical path for the high-value utilization of EVA waste and has good application prospects.
[0063] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for modifying waste EVA, characterized in that: The steps include: Firstly, waste EVA is placed in a supercritical CO2 environment for supercritical treatment, and then the waste EVA is modified by using microcrystalline cellulose to obtain modified waste EVA.
2. The method for modifying waste EVA according to claim 1, characterized in that: The conditions of the supercritical treatment are as follows: The temperature is 40-60°C, the pressure is 15-25MPa, and the time is 2-4h.
3. The method for modifying waste EVA according to claim 1, characterized in that: The method also includes a plasma treatment performed synchronously with the supercritical treatment, wherein the plasma treatment is used to induce the grafting of functionalized monomers onto the waste EVA.
4. The method for modifying waste EVA according to claim 3, characterized in that: The functional monomer is acrylic acid or acrylamide.
5. The method for modifying waste EVA according to claim 4, characterized in that: The conditions of the plasma treatment are as follows: •The output power of the plasma generator is 50-200W, the gas used is a mixture of Ar and O2 in a volume ratio of 7:3-9:1, and the processing time is 15-45min.
6. The method for modifying waste EVA according to claim 1, characterized in that: The specific steps of modifying the waste EVA using microcrystalline cellulose are: The waste EVA is mixed with the microcrystalline cellulose, water and cellulase are added thereto, the pH value is adjusted to 4.8-5.2, and an enzymatic hydrolysis reaction is carried out under stirring conditions; After the enzymatic hydrolysis reaction is completed, the reaction temperature is rapidly raised to 90° C. and maintained for 10 minutes, and then the product obtained by the reaction is dried to obtain the modified waste EVA.
7. The method for modifying waste EVA according to claim 6, characterized in that: The mass ratio of the waste EVA to the microcrystalline cellulose is 1-3:
20.
8. A modified waste EVA, which is prepared by the modification method described in any one of claims 1 to 7.
9. An EVA product prepared by using the modified waste EVA according to claim 7, characterized in that: The invention comprises the following raw materials in parts by weight: Modified waste EVA 40-60 parts, EVA 30-50 parts, foaming agent 2-4 parts, cross-linking agent 1-3 parts, seaweed powder 5-10 parts, processing aid 1-5 parts.
10. A method for preparing an EVA product as claimed in claim 9, characterized in that: The steps include: The modified waste EVA is mixed with other raw materials in proportion, and subjected to banburying treatment and foaming treatment to prepare EVA products.